Molecular modeling studies and in vitro screening of dihydrorugosaflavonoid and its derivatives against mycobacterium tuberculosis - Puranik, Ninad V.; Srivastava, Pratibha; Swami, Sagar; Choudhari, Amit; Sarkar, Dhiman (RSC Advances, 2018)
Novel drug regimens against tuberculosis (TB) are urgently needed and may be developed by targeting essential enzymes of Mtb that sustain the pathogenicity of tuberculosis. In the present investigation, series of compounds (5a-f and 6a-f) based on a naturally occurring rugosaflavonoid moiety were evaluated by in silico molecular modeling studies against -ketoacyl-ACP reductase (MabA) (PDB ID: IUZN) and pantothenate kinase (PanK) (PDB ID: ; 3AF3). Compounds 5a, 5c, 5d, and 6c, which had docking scores of -8.29, -8.36, -8.17 and -7.39 kcal mol(-1), respectively, displayed interactions with MabA that were better than those of isoniazid (-6.81 kcal mol(-1)). Similarly, compounds 5a, 5c, 5d, and 6c, which had docking scores of -7.55, -7.64, -7.40 and -6.7 kcal mol(-1), respectively, displayed interactions with PanK that were comparable to those of isoniazid (-7.64 kcal mol(-1)). Because of their docking scores, these compounds were screened in vitro against Mycobacterium tuberculosis H37Ra (Mtb) using an XRMA protocol. Among the screened compounds, the dihydrorugosaflavonoid derivatives 5a, 5c, and 5d had IC50 values of 12.93, 8.43 and 11.3 g mL(-1), respectively, and exhibited better inhibitory activity than the parent rugosaflavonoid derivatives. The rugosaflavonoid derivative 6c had an IC50 value of 17.57 g mL(-1). The synthesized compounds also displayed inhibitory activity against the Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.

Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis

First synthesis of podocarflavone A and its analogs and evaluation of their antimycobacterial potential against mycobacterium tuberculosis with the support of virtual screening - Puranik, Ninad V.; Swami, Sagar; Misar, Ashwini V.; Mamgain, Ritu; Gulawani, Swapnaja S.; Dhiman, Sarkar; Srivastava, Pratibha (Natural Product Research, 2022)
The first synthetic route developed for Podocarflavone A reported from Podocarpus macrophyllus and its analogs in 7 steps. Computational analysis for binding with the pantothenate kinase (3AVO) of Mycobacterium tuberculosis showed their docking score (ds) in the range of -8.9 to -9.3 Kcal/mol. MD simulations delineated the stability of the protein-ligand complexes in the TIP3P model. MMGBSA and MMPBSA values of 8d were -42.46 Kcal/mol and -14.58 Kcal/mol, respectively. Further in-vitro antitubercular screening of compounds 8a, 8d, and 8e against M. tuberculosis H37Ra using XRMA protocol exhibited promising antimycobacterial activity with IC50 values 21.82 mu g/mL, 15.55 mu g/mL, and 16.56 mu g/mL, respectively. Compounds 8a, 8d, and 8e showed antibacterial activity with IC50 values 41.56 mu g/mL, 24.72 mu g/mL, and 72.45 mu g/mL respectively against the Staphylococcus aureus. 8a and 8d showed inhibition with IC50 values 39.6 mu g/mL and 27.64 mu g/mL, respectively, against Bacillus subtilis. The present study could help in the further development of lead molecules against tuberculosis.
Keywords: and MMGBSA; antimycobacterial activity; docking; MD simulations; MMPBSA; Podocarflavone A synthesis

Design, synthesis, and in vitro biological evaluation of ROS-generating phenanthridin-trione-epoxide conjugates as agents against mycobacterium tuberculosis - Mamgain, Ritu; Swami, Sagar; Sarkar, Dhiman; Srivastava, Pratibha (ChemistrySelect, 2023)
Tuberculosis (TB) is one of the devasting infectious diseases and continues to spread among people despite having several specific drugs. Total eradication of TB is one of the shared interests of both the World Health Organization (WHO) and India globally. A library of antitubercular 6-((1-(aryl/heteroaryl)-1H-1,2,3-triazol-4-yl)methyl)oxireno[2,3-b] phenanthridine-5,7,9(6H,7aH,8aH)-trione (6 a-e) has been prepared in five steps including click chemistry and tested against active and dormant strains of Mycobacterium tuberculosis H37Ra using XRMA protocol. The result showed the inhibitory potential of 6 d IC50 at 0.74 & mu;g/mL concentration against active strain and at 0.9 & mu;g/mL against the dormant strain of Mtb. ROS generating ability of the compounds has been confirmed by luminol, H2O2, and glutathione assays. The molecular docking with the thioredoxin protein of Mtb showed a docking score of -9.6 Kcal/mol. To understand the mechanism with the thioredoxin protein of Mtb, the adduct formation of compounds with cystine was confirmed with HPLC. The involvement of lead molecules with existing drugs can be helpful in the eradication of tuberculosis.
Keywords: antimycobacterial agents; Computational docking; Cystine adduct; Epoxy-Phenanthridinone-triazoles; ROS generation

Coumarin hybrids: dual-target candidates for future antimicrobial and antitubercular therapies - Bavishi, Abhay; Vala, Hardev; Thakrar, Shailesh; Swami, Sagar; Sarkar, Dhiman; Shukla, Rushit; Kamdar, Jignesh; Shah, Anamik (Future Medicinal Chemistry, 2025)
Aims: This study aimed to synthesize, characterize, and evaluate the antimicrobial and antitubercular activities of two novel series of coumarin-based derivatives (Series 5 and Series 9), focusing on their structure-activity relationship (SAR) and molecular docking interactions with key bacterial enzymes. Materials & methods: Series 5 (5a-5j) and Series 9 (9a-9t) compounds were synthesized and characterized using spectroscopic techniques. Their antimicrobial and antitubercular activities were evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, Bacillus subtilis, and E. coli. IC50 values were determined, and molecular docking studies were conducted to assess binding interactions with M. tuberculosis enoyl-ACP reductase (InhA) and E. coli DNA gyrase B. Results: Series 5 compounds exhibited moderate activity, with 5f, 5 g, 5i, and 5j showing notable inhibition. Series 9 derivatives displayed superior dual-target inhibition, with 9t, 9c, 9a, 9b, and 9p achieving >90% inhibition against S. aureus and B. subtilis. The lowest IC50 against M. tuberculosis was observed for 9c (1.50 mu g/mL), followed by 9a (2.84 mu g/mL) and 9b (2.73 mu g/mL). Molecular docking confirmed strong binding interactions, correlating with observed biological activities. Conclusions: Series 9 compounds, particularly 9t, 9c, and 9a, demonstrate high potential as dual-target antimicrobial drug candidates. Further optimization may enhance their therapeutic efficacy. [GRAPHICS]
Keywords: Antimicrobial activity; antitubercular agents; Coumarin derivatives; Molecular docking studies; structure-activity relationship (SAR); thiophene-based compounds

Regio selective synthesis of pyrazole derivatives of 5-chloro-2-methoxy phenyl hydrazide and their biological evaluation - Bavishi, Abhay; Vala, Hardev; Swami, Sagar; Thakrar, Shailesh; Shah, Anamik; Sarkar, Dhiman (Journal of Heterocyclic Chemistry, 2025)
Present study involves synthesis of derivatives of (5-chloro-2-methoxyphenyl) (5-alkyl-3-(substituted) (phenyl/alkyl)-1H-pyrazol-1-yl) methanones. Structural elucidation of the synthesized compounds was depicted by the data of 1H and 13C NMR, IR, and Mass spectral analysis. The newly synthesized compounds 1a-1d and 2a-2i were screened in vitro against Mycobacterium tuberculosis H37Ra using an established XRMA protocol. Among the screened compounds, 2d, 2f, and 2h showed good percent inhibition against the active stage of M. tuberculosis H37Ra 80.77, 55.70, and 79.54, respectively, at 30 mu g/mL of inhibitor concentration. Further in secondary screening, compound 2d exhibited significant antitubercular activity on the active stage of M. tuberculosis H37Ra with IC50 of 0.208 mu g/mL. The synthesized compounds were also screened for antibacterial activity and found no significant activity against Gram-positive Bacteria Bacillus subtitles and Staphylococcus aureus and Gram negative bacteria Pseudomonas aeruginosa and Escherichia coli at 30 mu g/mL, which confirms the specificity of inhibitory activity against M. tuberculosis and more selectively against the active stage. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.
Keywords: 5-chloro-2-methoxy phenyl hydrazide; antibacterial activity; Antitubercular activity; Biological evaluation; H37Ra; hydrazide; Pyrazole

Synthesis, biological screening, and molecular docking of hybrid pyrazole scaffolds for antitubercular and antimicrobial activity - Bavishi, Abhay; Vala, Hardev; Radadiya, Ashish; Swami, Sagar; Thakrar, Shailesh; Sarkar, Dhiman; Shah, Anamik (ChemistrySelect, 2025)
This study reports the synthesis, characterization, and docking analysis of 21 novel compounds, including asymmetric dihydropyridines (4a-4o) and chalcones (6a-6f), derived from coupling 1,3-(substituted)-diphenyl-1H-pyrazole-4-carbaldehyde with active methylene compounds and 3-acetyl-4-hydroxycoumarin, respectively. Structural confirmation was achieved through 1H and 13C NMR, IR, and mass spectrometry. Biological screening against mycobacterium tuberculosis H37Ra identified compounds 4b, 4d, 4f, 4g , 4i, 4k, 6e, and 6f as significant antitubercular agents. Antibacterial evaluation at 30 mu g/mL showed selective inhibition of gram-positive bacteria, with compound 6e active against Staphylococcus aureus and Bacillus subtilis, and 6f showing activity specifically against S. aureus. Docking studies indicated effective InhA binding (Delta G = -3.52 to -7.27 kcal/mol) and inhibition constants ranging from 2640 to 4.71 mu M. Key binding interactions with residues TYR156 and ILE192 were observed, enhancing affinity, particularly for compound 6e. The SAR analysis emphasized the enhanced antitubercular potency of 2-chloroacetyl and 2,4-dichlorobenzoyl substitutions in the dihydropyridine series, while in the chalcone series, specific substitutions, such as the 3-nitro substitution in 6e, enhance antitubercular and antimicrobial potency due to stronger hydrogen bonding and increased polar surface area, while the 4-fluoro substitution in 6f confers selective activity against S. aureus.
Keywords: 1; 4-dihydropyridine; 4-hydroxy coumarin; Biological activity; In silco studies; Pyrazole